The NSUN5 gene rs1880948 A>G polymorphism and neuroblastoma risk in Chinese children - Ye, Zijie; Zeng, Huijuan; Zheng, Manna; Hu, Chao; Pan, Jing; Yang, Jiliang; Tan, Tianbao; Zhou, Chunlei; He, Jing; Zou, Yan; Yang, Tianyou (Frontiers in Oncology, 2025)
BackgroundNeuroblastoma (NB) is the most common extracranial solid tumor in children. The 5-methylcytosine (m5C) modification gene NSUN5 polymorphisms may serve as promising molecular markers for identifying populations susceptible to NB.MethodTaqMan probes were used to genotype NSUN5 single nucleotide polymorphisms (SNPs) in 402 NB patients and 473 healthy controls. A logistic regression model was applied to calculate the odds ratio (OR) and 95% confidence interval (CI) to evaluate the association between genotype polymorphisms and NB susceptibility. The analysis was further stratified by age, gender, tumor origin site, and clinical stage.ConclusionIn summary, our study indicates that the selected NSUN5 rs1880948 A>G polymorphisms may not be associated with neuroblastoma susceptibility. However, further studies with larger sample sizes and additional potentially functional polymorphisms are needed to validate these results.